2013
DOI: 10.3855/jidc.3079
|View full text |Cite
|
Sign up to set email alerts
|

Malaria elimination: needs assessment and priorities for the future

Abstract: When the World Health Organization announced the goal of global eradication of malaria in 2007, questions were raised about the naivety of this proposition. Since then, experts have been divided about this goal. Some scientists suggest that when defeating malaria, elimination is a worthy and challenging aim, but this has to be done with modesty and thorough analysis. Others believe that it is time to repeat the experience of smallpox eradication and to open a whole new era for public health, the eradication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
0
16
0
2
Order By: Relevance
“…Congruent with El-Moamly’s 6 findings, which identified vector resistance to insecticides as a potentially serious obstacle to achieving malaria elimination, this study revealed that malaria researchers were concerned about the lack of preparedness with new alternative drugs and insecticides, should resistance to current drugs and insecticides occur. Although malaria researchers participating in this study acknowledged that their role in the implementation of a malaria elimination policy was advisory and supportive in nature, through which they are expected to produce research evidence to guide the elimination programme, 6 they argued that the current state of malaria research to guide malaria elimination in SA was poor. They attributed this problem to the funding constraints to conduct malaria research in the country.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Congruent with El-Moamly’s 6 findings, which identified vector resistance to insecticides as a potentially serious obstacle to achieving malaria elimination, this study revealed that malaria researchers were concerned about the lack of preparedness with new alternative drugs and insecticides, should resistance to current drugs and insecticides occur. Although malaria researchers participating in this study acknowledged that their role in the implementation of a malaria elimination policy was advisory and supportive in nature, through which they are expected to produce research evidence to guide the elimination programme, 6 they argued that the current state of malaria research to guide malaria elimination in SA was poor. They attributed this problem to the funding constraints to conduct malaria research in the country.…”
Section: Discussionmentioning
confidence: 91%
“…According to El-Moamly, 6 some experts viewed the proposition to eliminate malaria as naïve, whereas others were encouraged by eradication of small pox and believe that it can also be done with malaria. The anti-elimination group fears that if expectations to eliminate malaria are raised and fail again, that this may be a major setback to the malaria control community, in the light of the challenges experienced in the GMEP of 1955–1969.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…vivax em diferentes localidades requer ações integradas em diversas frentes, como a ampliação e fortalecimento dos programas de malária, desenvolvimento de novas ferramentas, especialmente de diagnóstico e tratamento, aliadas a um programa permanente e contínuo de política e financiamento (Cortter et al, 2013;Newby et al, 2016; WHO, 2016a). As intervenções na malária requerem um alto investimento econômico e promovem consideráveis retornos nos investimentos em saúde pública (Cortter et al, 2013;El-Moamly, 2013;Tusting et al, 2015). Há uma meta internacional da OMS de eliminar a malária em 35 países até 2030, posteriormente novas definições e estratégias deverão ser elaboradas e discutidas afim de planejamento para a eventual erradicação desta doença (Newby et al, 2016 (Moreira et al, 2015), portanto com capacidade de detecção do parasito em pacientes com baixa parasitemia, mas a interpretação dos resultados positivos ainda é discutida (Baum et al, 2016;Congpuong et al, 2012;Harris et al, 2010).…”
Section: Pilares Da Estratégia No Combate à Maláriaunclassified